Comparison of Efficacy of Two Suture Materials, i.e., Monofilament Suture and Multifilament Suture as Subcuticular Skin Stitches in Post-Cesarean Women: A Randomized Clinical Trial. - Gupta, Sonika; Mehta, Anil; Sharma, Raj Rishi; Sharma, Rishab (Asian Journal of Medical Research, 2018)
Background: Objective: To compare the efficacy of two suture materials, i.e., Monofilament Suture and Multifilament Suture, as subcuticular skin stitches in post-cesarean women. Study Design: This was a randomized clinical trial. Population The study was conducted in the department of obstetrics and gynecology of Government Hospital Gandhi Nagar, Jammu. Only those women undergoing emergency cesarean section were included. Subjects and Methods: The study was conducted in the department of obstetrics and gynecology of Government Hospital Gandhi Nagar, Jammu, India. 120 women undergoing emergency cesarean section were included and divided into two groups. In group 1, Monofilament suture (poliglecaprone 25) was used as subcuticular skin stitches; in group 2, Multifilament suture (polyglactin 910) was used as subcuticular skin stitches. Results: 36.6% of patients in group 2 had pain and tenderness as compared to 6.6% in group 1 on day 4. 10% had discomfort as compared to 6.6% in group 1 on day 4. In group 1, 6.6 % patients had swelling and indurations, while it was 3.3 % in group 2 on day 4. Wound dehiscence was 20% in group 2 as compared to 10% in group 1. Regarding wound healing, 93.3 % patients had excellent wound healing in group 1 and 66.6 % in group 2. Conclusion: It was concluded that complications like swelling and induration, wound discharge and wound dehiscence were significantly less in poliglecaprone as compared to polyglactin 910 group.